2019
DOI: 10.1097/ccm.0000000000003744
|View full text |Cite
|
Sign up to set email alerts
|

Original Intracerebral Hemorrhage Score for the Prediction of Short-Term Mortality in Cerebral Hemorrhage: Systematic Review and Meta-Analysis

Abstract: Objectives: To systematically assess the discrimination and calibration of the Intracerebral Hemorrhage score for prediction of short-term mortality in intracerebral hemorrhage patients and to study its determinants using heterogeneity analysis. Data Sources: PubMed, ISI Web of Knowledge, Scopus, and CENTRAL from inception to September 15, 2018. Study Selection: Adult studies validating the Intracerebral Hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…In patients with spontaneous ICH, a baseline severity score might be reasonable to provide a general framework for communication with the patient and their caregivers. 472,473 3: No Benefit B-NR 3. In patients with spontaneous ICH, a baseline severity score should not be used as the sole basis for forecasting individual prognosis or limiting life-sustaining treatment.…”
Section: B-nrmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with spontaneous ICH, a baseline severity score might be reasonable to provide a general framework for communication with the patient and their caregivers. 472,473 3: No Benefit B-NR 3. In patients with spontaneous ICH, a baseline severity score should not be used as the sole basis for forecasting individual prognosis or limiting life-sustaining treatment.…”
Section: B-nrmentioning
confidence: 99%
“…In patients with spontaneous ICH, administering a baseline measure of overall hemorrhage severity is recommended as part of the initial evaluation to provide an overall measure of clinical severity. [472][473][474] 2b B-NR 2. In patients with spontaneous ICH, a baseline severity score might be reasonable to provide a general framework for communication with the patient and their caregivers.…”
Section: B-nrmentioning
confidence: 99%
“… 28 Nevertheless, it is important to note that commonly used prognostic scores vary widely in their ability to predict outcome accurately, with a c-statistic varying from 0.62-0.88 for the prediction of 3- and 12-month mortality, 22 and may be particularly less reliable for the highest scores that predict poor outcome. 24 Only few of these scores can predict functional outcome beyond 30 days after symptom onset. 22 Although our study showed a relatively low percentage of physicians using a prediction tool, the factors age and GCS score, which are important components in all prediction scores, were considered important factors to influence decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,17,18 Prediction scores used in the acute phase have limited accuracy for the prediction of 30-day mortality and functional outcome, [19][20][21][22][23] and appear especially unreliable for the higher scores that predict poor outcome. 24 Furthermore, these prediction scores do not facilitate physicians in their choice for a certain treatment strategy. The decision to perform surgery for supratentorial sICH often depends on assumptions based on personal experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of cerebral hemorrhage has increased in recent years, and patients with cerebral hemorrhage are often in critical condition and exhibit varying degrees of disturbance in consciousness. 1 , 2 Pulmonary infection is a common and serious complication in patients with cerebral hemorrhage, and it is also a primary cause of multiple organ failure and death. 1 , 2 Previous studies have shown that the efficacy and safety of the antibiotic linezolid, a cost-effective option, were superior to those of vancomycin, 3–7 These results suggested that linezolid should be the first-line antibiotic for treatment of methicillin-resistant Staphylococcus aureus ( MRSA ).…”
Section: Introductionmentioning
confidence: 99%